Atypical hemolytic-uremic syndrome - A case series from a tertiary care hospital from Eastern India - Mukesh Kumar Jain; Nikunj Kishore Rout; Amit Ranjan Rup; Sibabratta Patnaik; Chinmay Kumar Behera; Reshmi Mishra; Bandya Sahoo (Wolters Kluwer Medknow Publications, 2021)
Atypical hemolytic-uremic syndrome (aHUS) is a form of thrombotic microangiopathy that occurs due to dysregulation of alternate pathway of complement system, which progressively causes systemic complications, end-stage renal disease, and death. As prognosis is poor compared to typical hemolytic-uremic syndrome, early diagnosis and treatment is crucial for favorable outcome. We came across seven patients of aHUS in our pediatric intensive care unit in the last 5 years. Plasma exchange (PE) along with immunosupressives was used for treatment. First child who did not receive PE died. Rest six patients underwent PE and attained hematological remission; however, one later on progressed to chronic kidney disease and expired. All others are on regular follow-up and doing well. A high index of suspicion is required to diagnose aHUS. Early PE can give a better prognosis.